Writing White at the Fault Line: Some Reflections on South African Literary Journalism. Issue 1 (2nd January 2019) - Scott, Claire
Abstract : By exploring the literary journalism of Rian Malan ( My Traitor's Heart ), Antje Krog ( Country of My Skull and Begging to Be Black ), Jonny Steinberg ( Midlands ) and Kevin Bloom ( Ways of Staying ), I seek to reflect upon the ways in which these writers are able to use the uncertainties and contradictions inherent in this genre to reveal the complexities of identity formation and negotiation within contemporary South African society. They are very often writing at times of political and social flux, and by writing at the unstable boundaries of literature and journalism these authors not only mirror the volatility of their social setting but also endeavour to find new narrative forms through which to address the complexities of white South African identity. By working at the fault line of literature and journalism, Krog, Bloom, Malan and Steinberg are seeking those points of intersection and interpenetration that create narrative instability and fluidity, in order simultaneously to reveal the inherent anxiety and possibility of the "inbetween." Finally, I suggest that the instability and liminality of "skin" offers a space in which white South African identities can become fluid rather than fixed, and in which whiteness can begin to move out from under the umbrella of its global sanctity and into "folded-togetherness" with its many "others"